THE SEMANTIC ASPECTS OF POEMS WRITTEN BY EIGHTH-GRADE STUDENTS OF HURRASUL AQIDAH TARAKAN AS A REPRESENTATION OF LOCAL WISDOM IN THE COASTAL REGION OF NORTH KALIMANTAN - Muhammad Ilham; Muhammad Refi Naldi (Universitas Muhammadiyah Makassar, 2026)
This study aims to examine the construction of meaning in poems written by eighth-grade students of Madrasah Hurrasul Aqidah Tarakan using Michael Riffaterre’s literary semiotic approach. The analysis focuses on the mechanisms of indirect expression, including displacement of meaning, distortion of meaning, and creation of meaning, as well as the process of meaning-making through heuristic and hermeneutic readings. In addition, the study explores the relationship between the meanings conveyed in the poems and the coastal cultural context of North Kalimantan, which forms part of the students’ social and cultural environment. This research employed a qualitative descriptive method with a field research design. Data were collected through poetry-writing tasks, observations, and documentation, and were analyzed through data reduction, data presentation, and conclusion drawing. The findings reveal that students construct meaning in their poems through the use of symbols, metaphors, and poetic expressions that represent emotional experiences such as struggle, longing, exhaustion, and hope. Displacement of meaning is reflected in the use of symbols that represent particular feelings and life experiences. Distortion of meaning appears in linguistic expressions that deviate from literal logic, thereby enhancing the aesthetic effect of the poems. Meanwhile, the creation of meaning is realized through repetition and the interconnectedness of meanings across lines and stanzas. The study also indicates the presence of North Kalimantan coastal cultural elements, represented through images of the sea, fishermen’s lives, and coastal environments. However, these local cultural aspects are not yet dominant, as most poems primarily focus on the students’ personal experiences. Therefore, Riffaterre’s semiotic theory proves relevant for uncovering meaning in students’ poetry and provides a foundation for developing literary learning that integrates aesthetic experience with local wisdom.